Transnational mobility desires and discourses: Young people from return‐migrant families negotiate intergenerationality, mobility capital, and place embeddedness - Ní Laoire, Caitríona (Population space and place, 2020)
A longitudinal and intergenerational perspective opens up possibilities of novel insights into the socio‐spatial practices and relations that constitute, and generate, transnational youth im/mobilities. This paper draws on research conducted over 10 years with young adults who had migrated to Ireland as children with their return‐migrant parents during the Celtic Tiger period. It explores how, as young adults, they envisage and navigate their unfolding im/mobility pathways. In a context where transnational mobility experience is highly valued and celebrated, they draw on their mobility capital as former migrants to self‐position as knowledgeable mobile subjects. However, precisely because of their personal and family mobility resources, their engagements with discourses of hypermobility are selective—simultaneously claiming the cultural capital of transnational mobility and de‐fetishising it by producing grounded interpretations that value place embeddedness. The paper sheds light on some of the tensions of contemporary youth mobilities in contexts of globalisation, uncertainty, and migration.